Metarhachotropis parva, a new genus and species of Eusiridae (Crustacea: Amphipoda) from Sagami Bay, central Japan - Ariyama, Hiroyuki; Kohtsuka, Hisanori (Zootaxa, 2022)
The monotypic genus Metarhachotropis (Crustacea: Amphipoda: Eusiridae) is erected with M. parva sp. nov. from Sagami Bay, central Japan, as its type species. This new genus is characterized by the massive head with large rostrum, the very short coxae and the strongly produced coxa 1. Metarhachotropis resembles Eusirella Chevreux, 1908 and Rhachotropis Smith, 1883; however, it can be distinguished from Eusirella by the ordinary length of the maxilla 1 palp, and from Rhachotropis by the smooth body.